Percutaneous Cervical Nucleoplasty in the Treatment of Cervical Disc Herniation, Clinical Results of Neck and Arm Pain - Siribumrungwong, MD, K; Tejapongvorachai, MD, T (Journal of Southeast Asian Orthopaedics, 2022)
Objective: To evaluate the efficacy of percutaneous cervical nucleoplasty in treatment of cervical disc herniation in neck and arm pain. Material and Method: Percutaneous cervical nucleoplasty was performed in 22 patients who had cervical disc herniation between April 2008 and February 2009. The clinical results in terms of clinical outcome were measured by the visual analogue scale (VAS) pain score preoperatively and at 1-week, 1-, 3-, 6-, and 12-month follow-ups. Results: The patient’s gender distribution for percutaneous cervical nucleoplasty (PCN) was 10 males and 12 females. The age of the patients ranged from 31 to 55 years, with a mean age of 41 ± 6.8 years. There were no recurrent cases or complications in this study. The mean preoperative neck pain and arm pain were 6.7 ± 1.2 and 8.5 ± 0.7. Whereas, the mean VAS pain scores of neck/arm pain postoperative at 1-week, 1-, 3-, 6-, and 12-month visits were 3.0/2.0, 3.9/1.7, 3.9/1.5, 4.1/2.0, and 3.6/2.1, respectively. There was statistically significant improvement in neck and arm pain after the surgical procedure (p<0.01). Conclusion: Percutaneous cervical nucleoplasty in cervical disc herniation resulted in a significance improvement of neck and arm pain in cervical disc herniation.